Digital Signal Processing : Theory And Practice
This concise and clear text is intended for a senior undergraduate and graduate level, one-semester course on digital signal processing. Emphasis on the use of the discrete Fourier transform (the heart of practical digital signal processing) and comprehensive coverage of the design of commonly used digital filters are the key features of the book. The large number of visual aids such as figures, flow graphs, and tables makes the mathematical topic easy to learn. The numerous examples and the set of Matlab programs (a supplement to the book) for the design of optimal equiripple FIR digital filters help greatly in understanding the theory and algorithms.